Microspheres: Microfluidic Generation of Monodisperse and Photoreconfigurable Microspheres for Floral Iridescence–Inspired Structural Colorization (Adv. Mater. 26/2016). Issue 26 (7th July 2016) - Yeo, Seon Ju; Park, Kyung Jin; Guo, Kai; Yoo, Pil J.; Lee, Seungwoo
Abstract : Flowering plants have advanced their colorization strategies to divide incoming white light into spatially sequenced vivid colors, especially by using 2D grating diffractive motifs. On page 5268, P. J. Yoo, S. Lee, and co‐workers conceive a new idea for a microfluidic approach to mimic this wonderful biological strategy and its practical application to the color encoding of colloidal particles.